THE EVOLUTION OF CONSUMER BEHAVIOR IN THE DIGITAL AGE: A SYSTEMATIC REVIEW OF E-COMMERCE MARKETING STRATEGIES - Akbar, Ilham (Penelitian dan Pengembangan Ilmu, 2024)
Real-time personalized marketing techniques are becoming important in improving consumer experience and driving impulse shopping behavior in digital e-commerce. However, the impact of these techniques on various cultural demographics remains underexplored, particularly in the context of consumer impulsivity. This research aims to systematically examine how real-time personalization influences impulse buying behavior in various cultural settings, using a systematic literature review approach. Through the PRISMA method, relevant studies are collected from databases such as Scopus, Web of Science, and JSTOR. Key findings suggest that cultural values ​​significantly moderate responses to real-time personalization, with consumers from individualist cultures showing higher levels of impulsivity compared to collectivist cultures. This research contributes to the e-commerce literature by identifying cultural dynamics in real-time personalization strategies, providing practical insights for marketers to design adaptive and effective personalization strategies in global markets.